Multimodal and ubiquitous computing systems supporting independent-living older users. - Perry, M.
We document the rationale and design of a multimodal interface to a pervasive/ubiquitous computing system that supports independent living by older people in their own homes. The Millennium Home system involves fitting a resident's home with sensors-these sensors can be used to trigger sequences of interaction with the resident to warn them about dangerous events, or to check if they need external help. We draw lessons from the design process and conclude the paper with implications for the design of multimodal interfaces to ubiquitous systems developed for the elderly and in healthcare, as well as for more general ubiquitous computing applications.
Keywords: Millennium Home system; Healthcare; Independent-living older user; Interaction design; Multimodal computing; Multimodal interfaces; Older people; Own homes; Pervasive computing; Seniors; Sensors; Ubiquitous computing system